Skrining Kesehatan Dasar sebagai Upaya Deteksi Dini Status Gizi dan Tekanan Darah pada Siswa SMA 8 Muhammadiyah Kisaran - Wahidah Wahidah; Icmi Ikhtiari Nanjar; Fahnidar Rahmah; Fauziah Fauziah (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Adolescent health problems have become increasingly complex due to a shift from infectious diseases to non-communicable diseases (NCDs), which often begin during school age, with nutritional status and blood pressure serving as key risk indicators. This community service activity aimed to describe the nutritional status and blood pressure profile of students at SMA 8 Muhammadiyah Kisaran as an effort for early detection of NCD risk. A descriptive study design with a basic health screening approach was employed, involving cross-sectional measurements of Body Mass Index (BMI) and blood pressure among 91 students selected through total sampling. The results showed that most students had normal nutritional status (47.3%); however, notable proportions were classified as underweight (19.8%), overweight (22.0%), and obese (11.0%). Cases of prehypertension and hypertension were more frequently observed among students with overweight and obese BMI categories. These findings indicate a tendency toward increased risk of blood pressure disorders as BMI increases in adolescents. In conclusion, basic health screening is an effective tool for mapping adolescent health risks and provides an important foundation for planning school-based promotive and preventive health programs. Therefore, routine screening integrated with nutrition education, physical activity promotion, and appropriate health follow-up for at-risk students is strongly recommended